Construction and reliability of labeled magnitude satiety scale for Malay population - Zalifah Mohd Kasim,; Asma Qamaliah Abdul Hamid,; Razalee Sedek, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Satiety is a persistent feeling of fullness after a meal that can prevent further energy consumption until hunger is felt again. This study was conducted to construct and validate the reliability of a labeled magnitude scale (LMS) in the Malay language among Malay adult population in Universiti Kebangsaan Malaysia. A total of 100 subjects rated the semantic meaning of 40 Malay phrases describing different levels of satiety and hunger using magnitude estimation. Eleven anchor phrases were positioned corresponding to their geometric mean magnitude to construct a bipolar LMS satiety scale. Thirty subjects have taken part in food testing (commercial breakfast cereal) for reliability using the LMS scale from this study and reference scale in two occasions, one week apart from one another. Evaluations were made at 0 min, each 15 min for the first 90 min and each 30 min until 180 min. The results showed significant differences (p<0.05) between male and female subject for two positive (satiety) and negative (hunger) anchor phrases. During food test evaluation, the male subject showed a shorter time to reach a neutral point (not hungry nor fullness) compared to female subject in both studies. The alpha value between LMS in this research and reference is 0.907. Therefore, the reliability for the label magnitude scale in this study is high which indicated the scale is very suitable and reliable for Malay subjects in Malaysia to evaluate their perception of fullness and hunger after meal consumption.